Penerapan Regresi Binomial Negatif dalam Memodelkan Angka Kelahiran Remaja Usia 15-19 Tahun di Indonesia pada Tahun 2017 - Zahra Tiara Aini; Anneke Iswani Achmad (UNISBA Press, 2022)
Abstract. Poisson regression is a method to analyze the relationship between the independent variable and the dependent variable, which is discrete. In Poisson regression, it must meet the assumption of equidispersion, namely the assumption that the variance and average values of the data are the same. However, discrete data often experiences overdispersion conditions, namely a situation where the variance value is greater than the average. A good alternative regression model for data experiencing overdispersion conditions is a negative binomial regression model that can model data experiencing overdispersion without having to eliminate the overdispersion condition originating from the data. The purpose of this study is to obtain results from the application of negative binomial regression in modeling the birth rate of adolescents aged 15–19 years in Indonesia in 2017 and to find out what factors significantly influence the birth rate of adolescents aged 15–19 years in Indonesia in 2017. From the analysis results, the negative binomial regression model is = exp(5,075 – 4,187×10-2X1 + 8,994×10-3X2 – 3,223×10-7X3 – 4,722X4 + 5,935×10-2X5) and the best negative binomial regression model is = exp(4,750808 + 0,012731X2 – 5,088598X4 + 0,066272X5). Based on the test results, it was found that the Gini index and the percentage of the female population aged 15–19 years who were ever married had a significant effect on the birth rate of adolescents aged 15–19 years in Indonesia in 2017. Abstrak. Regresi Poisson adalah suatu metode untuk menganalisis hubungan antara variabel bebas dengan variabel terikat yang bersifat diskrit. Pada regresi Poisson harus memenuhi asumsi equidispersi yaitu asumsi nilai varians serta rata-rata dari data adalah sama. Namun, pada data diskrit tak jarang mengalami kondisi overdispersi yaitu keadaan dimana nilai varians lebih besar dari rata-rata. Model regresi alternatif yang baik untuk data yang mengalami kondisi overdispersi adalah model regresi binomial negatif yang dapat memodelkan data yang mengalami overdispersi tanpa harus menghilangkan kondisi overdispersi yang berasal dari data. Tujuan dari penelitian ini adalah memperoleh hasil dari penerapan regresi binomial negatif dalam memodelkan angka kelahiran remaja usia 15-19 tahun di Indonesia pada tahun 2017 serta mengetahui faktor apa saja yang berpengaruh secara signifikan terhadap angka kelahiran remaja usia 15-19 tahun di Indonesia pada tahun 2017. Dari hasil analisis diperoleh model regresi binomial negatif nya adalah = exp(5,075 – 4,187×10-2X1 + 8,994×10-3X2 – 3,223×10-7X3 – 4,722X4 + 5,935×10-2X5) dan model regresi binomial negatif terbaik nya adalah = exp(4,750808 + 0,012731X2 – 5,088598X4 + 0,066272X5). Berdasarkan hasil pengujian, diperoleh indeks gini dan persentase penduduk perempuan berusia 15-19 tahun yang pernah kawin berpengaruh secara signifikan terhadap angka kelahiran remaja usia 15-19 tahun di Indonesia pada tahun 2017.